OS 28-02 RENAL DENERVATION ALTERS ADIPOKINE LEVELS IN PATIENTS WITH RESISTANT HYPERTENSION. (September 2016) - Schlaich, Markus; Hering, Dagmara; Marusic, Petra; Walton, Antony; Lambert, Elisabeth; Krum, Henry; Lambert, Gavin; Esler, Murray; Eikelis, Nina
Abstract : Objective: We have previously demonstrated the effectiveness of renal denervation (RDN) to lower blood pressure (BP) in part via the reduction of renal sympathetic activity. The aim of this study was to examine the effect of RDN on adipokines. In particular, whether BP reduction, associated with RDN treatment, has a favorable outcome on adipokine profile in patients with resistant hypertension (RH). Design and Method: Fifty seven patients with RH undergoing RDN have been recruited for the study (65% males, age 60.8 ± 1.5 years, BMI 32.6 ± 0.7 kg/m 2, mean ± SEM). At recruitment the patients were on an average of 4.8 ± 2.1 antihypertensive drugs and were asked o refrain from the changing their medication regimen for the duration of the study. Automated seated office BP measurements were taken with an Omron HEM-705 monitor at baseline and 3 months follow up visit. Leptin, insulin, non-esterified fatty acids (NEFA), adiponectin and resistin were measured in plasma at baseline and 3 months after RDN. Results: There was a significant reduction in mean office systolic (168.75 ± 2.57 vs 155.2 ± 3.2 mmHg, p < 0.001) and diastolic (90.7 ± 2.3 vs 83.7 ± 2.4 mmHg, p < 0.001) BP 3 months after RDN. Body weight and heart rate remained unchanged. There were no significant differences in plasma leptin levels post RDN. Fasting insulin concentration significantly increased 3 months after the procedure (20.05 ± 1.46 vs 29.70 ± 2.51 uU/ml, p = 0.002). There was a significant drop in circulating NEFA at follow up (1.01 ± 0.07 vs 0.47 ± 0.04 mEq/l, p < 0.001). While there were no changes in resistin, adiponectin concentration was significantly higher after RDN (5654 ± 800 vs 6644 ± 967ng/ml, p = 0.024). Conclusions: Our findings confirm previous reports of the effects of RDN on the reduction of BP. In addition, this is the first study to demonstrate that RDN is associated with potentially beneficial effects on the adipokine profile. Increased adiponectin and reduced NEFA production may contribute to BP reduction via metabolic pathways.